New design for an integrated Fourier transform spectrometer - Manzardo, Omar; Herzig, Hans-Peter; Guldimann, Benedikt; Marxer, Cornel; de Rooij, Nicolaas F. (My University, 2000)
We present a miniaturized Fourier transform (FT) spectrometer based on silicon micromachined. The FTS is a Michelson interferometer with one scanning mirror. The motion of the mirror is carried out by a n electrostatic comb drive actuator. The mirror displacement is 39 micrometers and its reproducibility is +/- 13 nm, which leads to a resolution better than 10 nm in the visible wavelength range. A new design of this chip has been realized in order to integrate an input fiber, a collimating lens system as well as a beam splitting plate. This new design allows to undertake spectroscopy with white light. The limitation of light collimation and the effect of the size of the source have been studied by numerical simulations.
Keywords: Fourier spectroscospy; actuator; MOEMS